Pullout behaviour of GFRP bars with anchor head in geopolymer concrete. (15th November 2015) - Maranan, G.B.; Manalo, A.C.; Karunasena, W.; Benmokrane, B.
Abstract: The geopolymer concrete internally reinforced with fibre-reinforced polymer (FRP) bars is anticipated to offer durable, sustainable, and cost-effective civil infrastructures. In this study, the effect of the anchor head on the pullout behaviour of the sand coated glass-fibre-reinforced polymer (GFRP) bars embedded in the geopolymer concrete was investigated using a direct pullout test. Straight and headed GFRP bars with different nominal diameters ∅ (12.7, 15.9, and 19.0 mm) and embedment lengths ld (0 ∅  +  lah, 5 ∅  +  lah, and 10 ∅  +  lah for headed bars, where lah stands for the anchor head length, and 5 ∅ and 10 ∅ for straight bars) were considered. The results showed that the provision of anchor head is an efficient method to enhance the anchorage capacity of GFRP bars in geopolymer concrete. The anchor heads improved the anchorage of the sand coated GFRP bars by as much as 49–77%. Furthermore, the mechanical bearing resistance provided by the anchor head alone resulted in the development of approximately 45% of the GFRP bars' nominal tensile strength. A comparison of the experimental results with the published studies showed that a much higher load is required to pullout the GFRP bars in geopolymer concrete than in Ordinary Portland Cement-based concrete.